Affordances for Fun: Applying Affordances to Video Game Interface Design - Bouchard, Matthew (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Video games can teach us a lot about building better interfaces, especially games that are played primarily in menu-style interfaces. This paper explores how these interface-based games can be better understood using the concept of affordances. Les jeux vidéo peuvent nous en apprendre beaucoup sur la conception d’interfaces améliorées, particulièrement les jeux qui se jouent par interfaces à menu. Cette communication explore comment ces jeux vidéo à interface peuvent nous offrir une meilleure compréhension du concept de capacité suggestive d’action.